Cellular responses in the Malpighian tubules of Scaptotrigona postica (Latreille, 1807) exposed to low doses of fipronil and boric acid - Ferreira, Rafael Alexandre Costa [UNESP]; Silva Zacarin, Elaine Cristina Mathias; Malaspina, Osmar [UNESP]; Bueno, Odair Correa [UNESP]; Tomotake, Maria Eliza Miyoko; Pereira, Andrigo Monroe [UNESP] (Elsevier, 2013)
Studies of sub-lethal effects of pesticide residues on stingless bees are scarce and morphological analysis of organs would add information to toxicological analysis in order to clarify the continuous exposure of Scaptotrigona postica to insecticides. The aim of this study was to evaluate the morphology and histochemistry of the Malpighian tubules (excretory organ) of S. postica exposed to fipronil or boric acid to detect cellular responses that indicate toxicity or adaptative mechanisms to stress induced by exposure of worker bees to low doses of these chemical compounds. Newly emerged bees were submitted to toxicological bioassays and morphological analyses by optical microscopy and Transmission Electron Microscopy, as well as histochemical methods, were performed to detect proteins and glycoconjugates. Additionally, immunohistochemical detection of DNA fragmentation and HSP70 (70-kDa Heat shock protein) were performed to detect cell death and stress response, respectively. Statistical analysis, for the bioassays conducted with ingestion of contaminated diet with boric acid at 0.75% (w/w) or with fipronil at 0.1μg/kg of food, showed that the survival of bees that ingested the contaminated diets were significantly different to the survival rate presented by the control group (P<0.0001). Although some characteristics indicative of initiation of cell death were observed, the cells remained metabolically active in the processes of excretion and inactivation of chemical compounds. The data from this study reinforce the importance of research on sublethal effects of low doses of pesticides on bees in an attempt to assess a possible realistic dose and evaluate the risk assessment of stingless bee S. postica foraging in the vicinity of cultivated fields and/or in green urban areas. © 2013 Elsevier Ltd.
Keywords: Boric acid and morphology; Fipronil; Inseticides; Malpighian tubules; Scaptotrigona postica; Continuous exposure; Histochemical methods; Morphological analysis; Toxicological analysis; Biochemistry; Boric acid; Cell death; Chemical compounds; Morphology; Nutrition; Optical microscopy; Pesticides; Proteins; Risk assessment; Toxicity; Transmission electron microscopy; Boride coatings; boric acid; fipronil; heat shock protein 70; insecticide; pyrazole derivative; animal; bee; cytochemistry; DNA fragmentation; drug effect; immunohistochemistry; Malpighian tubule; transmission electron microscopy; ultrastructure; Animals; Bees; Boric Acids; DNA Fragmentation; Histocytochemistry; HSP70 Heat-Shock Proteins; Immunohistochemistry; Insecticides; Malpighian Tubules; Microscopy, Electron, Transmission; Pyrazoles; Apoidea; Meliponinae